Stratigraphy of the Anthropocene - Zalasiewicz, J; Williams, M; Fortey, R; Smith, A; Barry, TL; Coe, AL; Bown, PR; Rawson, PF; Gale, A; Gibbard, P; Gregory, FJ; Hounslow, MW; et al. (ROYAL SOC, 2011)
The Anthropocene, an informal term used to signal the impact of collective human activity on biological, physical and chemical processes on the Earth system, is assessed using stratigraphic criteria. It is complex in time, space and process, and may be considered in terms of the scale, relative timing, duration and novelty of its various phenomena. The lithostratigraphic signal includes both direct components, such as urban constructions and man-made deposits, and indirect ones, such as sediment flux changes. Already widespread, these are producing a significant 'event layer', locally with considerable long-term preservation potential. Chemostratigraphic signals include new organic compounds, but are likely to be dominated by the effects of CO2 release, particularly via acidification in the marine realm, and man-made radionuclides. The sequence stratigraphic signal is negligible to date, but may become geologically significant over centennial/millennial time scales. The rapidly growing biostratigraphic signal includes geologically novel aspects (the scale of globally transferred species) and geologically will have permanent effects.